2019
DOI: 10.1080/21691401.2019.1699811
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic p27 is a novel prognostic biomarker and oncogenic protein for nasopharyngeal carcinoma

Abstract: Cytoplasmic p27 plays an important role in regulating the cell cycle. Recent studies have revealed p27 protein translocation from the nucleus to the cytoplasm in many tumour cells. The aim of this study was to investigate the role and molecular mechanisms of cytoplasmic p27 in the progression of nasopharyngeal carcinoma (NPC) and to explore its prognostic value. We found increased cytoplasmic p27 expression by immunohistochemistry in NPC tissues, and its expression level was significantly correlated with the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Nuclear translocation of p27 protein is also observed, which demonstrates apoptotic signaling in cancer cells. High level of p27 in cytoplasm may induce antiapoptotic signal in tumor cells but inhibits CDK2 and acts as tumor suppressor in nucleus [ 57 , 58 ]. These results suggest that activation of FOXO3 by regulation of MAPK and Akt pathways is essential for apoptotic effect of acetylshikonin in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear translocation of p27 protein is also observed, which demonstrates apoptotic signaling in cancer cells. High level of p27 in cytoplasm may induce antiapoptotic signal in tumor cells but inhibits CDK2 and acts as tumor suppressor in nucleus [ 57 , 58 ]. These results suggest that activation of FOXO3 by regulation of MAPK and Akt pathways is essential for apoptotic effect of acetylshikonin in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…We found that nuclear translocation of p27 was also occurred by acetylshikonin treatment (Figure 9), which results in suppression of cell cycle progression and induction of apoptosis. Overexpression of cytoplasmic p27 may inhibit apoptosis in tumor cells, via mediating activation of Akt, which is a canonical suppressor protein of apoptosis, and inhibition of cytochrome c release and caspase activation [54,55]. Despite these properties in the cytoplasm, p27 acts as an inhibitor of CDK2 when localized in the nucleus [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear translocation of p27 was found to be induced by BCA treatment, which resulted in the inhibition of the cell cycle and induction of apoptotic cell death. The accumulation of cytoplasmic p27 might suppress apoptosis in cancer cells via its association with the activation of Akt, which is a typical suppressor protein of apoptotic cell death and inhibition of cytochrome release and caspase activation [ 44 , 45 ]. Although these characteristics are present in the cytoplasm, p27 inhibits cyclin-dependent kinase 2 when localized in the nucleus [ 46 ].…”
Section: Discussionmentioning
confidence: 99%